Reelin Exerts Structural, Biochemical and Transcriptional Regulation Over Presynaptic and Postsynaptic Elements in the Adult Hippocampus - Bosch, Carles; Muhaisen, Ashraf; Pujadas, Lluís; Soriano, Eduardo; Martínez, Albert (Frontiers in Cellular Neuroscience, 2016)
Reelin regulates neuronal positioning and synaptogenesis in the developing brain, and adult brain plasticity. Here we used transgenic mice overexpressing Reelin (Reelin-OE mice) to perform a comprehensive dissection of the effects of this protein on the structural and biochemical features of dendritic spines and axon terminals in the adult hippocampus. Electron microscopy (EM) revealed both higher density of synapses and structural complexity of both pre- and postsynaptic elements in transgenic mice than in WT mice. Dendritic spines had larger spine apparatuses, which correlated with a redistribution of Synaptopodin. Most of the changes observed in Reelin-OE mice were reversible after blockade of transgene expression, thus supporting the specificity of the observed phenotypes. Western blot and transcriptional analyses did not show major changes in the expression of pre- or postsynaptic proteins, including SNARE proteins, glutamate receptors, and scaffolding and signaling proteins. However, EM immunogold assays revealed that the NMDA receptor subunits NR2a and NR2b, and p-Cofilin showed a redistribution from synaptic to extrasynaptic pools. Taken together with previous studies, the present results suggest that Reelin regulates the structural and biochemical properties of adult hippocampal synapses by increasing their density and morphological complexity and by modifying the distribution and trafficking of major glutamatergic components.